June jam - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House Children's Books, 2011)
As a Father's Day gift to the twins' Dad, Bradley, Brian, and their cousins Lucy and Nate try to identify and stop whatever creature is biting fruits and vegetables in the garden.
"A Stepping Stone Book."
"With the younger siblings of the A to Z mysteries kids!"- -Cover.
Keywords: Gardens -- Fiction; Pests -- Fiction; Father's Day -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Cousins -- Fiction; Mystery and detective stories